Emergence of Dengue Virus Serotypes 1 and 3 in Mahottari and Adjacent Areas of Southern Nepal - Sabin Shrestha; Sandesh Rimal; Anjana Kharbuja; Manoj Kumar Ray; Susmita Shrestha; Anjali Dulal; Suprabha Subedi; Ashma Khadka; Nabaraj Adhikari; Meghnath Dhimal; Basu Dev Pandey; Takeshi Urano; et al. (Pathogens)
Dengue has been a serious public health concern in Nepal since the past few years, with concurrent big outbreaks occurring in 2022–2024. This cross-sectional study was conducted among febrile patients visiting hospitals in Mahottari district in southern Nepal. A total of 2141 dengue-suspected patients were investigated by routine laboratory assays and serological and molecular techniques, including real-time quantitative polymerase chain reaction (RT-qPCR). Among them, 455 (21.3%) were confirmed as dengue cases. The majority of dengue cases (435, 95.6%) had a primary dengue infection. The total bilirubin level was significantly higher in secondary dengue infection than in primary (p = 0.032). The major dengue virus (DENV) serotypes responsible for this outbreak were DENV-1 (45.5%) and DENV-2 (40.9%), while 13.6% patients had DENV-3 infection. DENV-3 infection showed a significantly higher viral load (median: 7.71 Log10 copies/mL; range: 6.48–7.94) compared to DENV-1 (6.72 Log10 copies/mL; 5.49–7.17) and DENV-2 (4.76 Log10 copies/mL; 2.32–6.96). Adult patients exhibited a significantly higher viral load than children (p = 0.035). NS1- and IgM-positive as well as admitted patients had a higher viral load (p < 0.05). Co-circulation of multiple serotypes (DENV-1, -2, -3) was confirmed with the first introduction of DENV-1 and DENV-3 in Mahottari and surrounding areas in the 2023 outbreak. Identification of the circulating DENV serotypes is crucial to understanding the epidemiological trend and dynamics of population immunity. These findings underscore the need of nation-wide integrated surveillance, including genomic data generation, in Nepal for disease control, prevention, and potential vaccine implication.